On the estimation of the consensus rate of convergence in graphs with persistent interconnections. Issue 1 (2nd January 2018) - Chowdhury, Nilanjan Roy; Sukumar, Srikant; Maghenem, Mohamed; Loría, Antonio
ABSTRACT: The aim of the current article is to establish myriad convergence rate estimates to consensus for time-varying graphs with persistent interaction. Several novel analysis methodologies for consensus protocols employing the notions of persistence of excitation and Lyapunov functions are provided. The estimates are compared with each other and existing literature. Numerical simulations on test examples are illustrated to support the theoretical findings.